Cuidado junto às mulheres em situação de prostituição: processos pedagógicos e transformação social - Silva, Fernanda Priscila Alves da (2010)
This study verifies and analyzes how to care for women in the situation of prostitution from the perspective of popular education, aiming at social transformation. It is, therefore, important to investigate what are the mechanisms of exploitation, the causes and challenges experienced by the women involved in prostitution, in addition to examining the possibility of an education process which highlights popular education and liberation and finally, to suggest lines of action for the development of work from this perspective. The theoretical study becomes concrete on topics such as: prostitution and the context of the women who are involved in it, popular education, pedagogy and the processes triggered from the perspective of social transformation, and spirituality from the perspective of care. To accomplish such a study, in addition to the literature search, field research is used undertaking data collection and gathering, by active listening, the life histories of the women. Through the results obtained in the research, proposals are presented for action with women in the situation of prostitution.